A National Study of Community Health Centers' Readiness to Address COVID‐19. (20th August 2020) - Damian, A.J.; Gonzalez, M.; Oo, M.; Anderson, D.
Abstract : Research Objective: Community health centers (CHCs) serve as the patient medical home for populations that are disproportionately more susceptible to COVID‐19; yet, there is a lack of understanding of the current efforts in place by CHCs across the United States working to prepare for and respond to the current pandemic. The purpose of this mixed‐methods assessment was to understand community health centers' needs and readiness to address COVID‐19. Study Design: We conducted a sequential explanatory mixed‐methods approach. A pilot‐tested, web‐based, cross‐sectional survey regarding organizational and individual staff needs, and best practices currently in place to prepare for and prevent spread of COVID‐19, was administered to and completed by 240 primary care employees from 201 organizations across 44 states, the District of Columbia, and Puerto Rico. Focus group interviews were subsequently conducted with a convenience sample (n = 39) from the survey respondents to understand the needs and current efforts in place by CHCs across the United States working to prepare for and respond to COVID‐19. We applied the transcript‐based analysis approach to the focus group data and derived themes using the constant comparative method. Population Studied: The majority of respondents (59%) held administrative leadership roles at their respective agencies, while the remainder of the participants served in patient‐facing roles as physicians (8%), nurses (13%), and medical support staff (20%). Over a third (38%) of the participants came from practices in the Northeast region of the country, with the rest of respondents coming from the West (19%), South (19%), and Midwest (23%) regions, and minor representation from Puerto Rico (1%). Principal Findings: Respondents identified guidance regarding COVID‐19 infection prevention and control (77.1%), safety precautions (72.1%), and screening, diagnostic testing, and management of patients (67.1%) as their major educational needs. Findings from the focus groups highlighted five key themes relevant to foundational aspects of readiness: leadership, communication, formal policies and procedures, resources, and workforce capacity. Responses from the focus groups clearly reflected the difficulty imposed on an already stretched, understaffed workforce in pivoting to rapidly address the expected surge in demand from patients related to the pandemic. Conclusions: The COVID‐19 pandemic has exacerbated long‐standing capacity issues that CHCs face, making it challenging for these safety‐net practices to adequately respond to the current disease outbreak. In addition to the more universal concerns about lack of testing and personal protective equipment, these findings highlight the special challenge posed by lack of staffing resources in CHCs as recruitment and retention of staff in rural and other medically underserved practice locations has burdened health centers long before the current pandemic. Implications for Policy or Practice: The COVID‐19 pandemic is occurring at a time when CHCs nationwide are experiencing great economic uncertainty. There is a need for Congress to prioritize reauthorization of funding for CHCs in order to prevent major hiring freezes, layoffs, and reduced patient care services, especially during a pandemic. Similarly, greater Federal financial support for CHCs is needed to ensure these practices have the capacity to continue serving the most vulnerable members of society, thereby helping relieve the stress on hospitals and flatten the spread of COVID‐19.